Vivenciar a doença: um estudo com portadores de doença renal crônica - Souza, Karen Susanne e [UNESP] (2015)
The non-communicable chronic diseases are public health problems worldwide . Among these, we find the chronic kidney disease, which causes physical, psychological and social damage to the bearer. The pair treatment CKD is divided into conservative and TRS treatment. The diagnosis of a chronic disease results several changes in the individual's daily life, often accompanied by psychological disorganization and varied emotional reactions. Thus, it is considered relevant to know and approach the patient, their perception and knowledge of the disease. This study aimed to identify the perception of the patient with chronic kidney disease (stages 3 and 4) and their experience about the same. It is a qualitative research, of descriptive nature, with patients suffering from CKD who have been treated at the Nephrology Clinic of the Hospital of the Medical School of Botucatu - UNESP. Semistructured interviews were conducted, which, with the amount of people to be interviewed determined by the saturation point. In total 14 people participated, 7 women and 7 men with medical age of 59.9 years. Most of them have lived with their spouse, have had family income of up to two minimum wages and had attended to complete primary school. Although most already follow a chronic disease (diabetes and or hypertension), the most intense concern about the treatment and adherence to medical recommendations effectively occur after diagnosis of CKD that happened, on average, 6.2 years ago .The interviewees had different feelings and experiences related to the disease. The DRC initially causes mixed feelings as resentment, sadness, and fear, that in some was later transformed into a more positive attitude to face. The main changes relate to own family relationship around the sick one, in addition to dietary restrictions and physical impairment. Thus, it was observed that experience the DRC, means facing physical, psychological and social changes, requiring a great ...